(465) Development of a dual economy تطوير اقتصاد مزدوج - ِAlavaro Chapatto (معهد التخطيط القومي, 2026)
abs The passage emphasizes that contemporary developing societies seek to achieve rapid economic and social progress by utilizing available resources in the most efficient and organized manner. This objective requires systematic planning to ensure that resources are allocated effectively and used at the appropriate time and in the proper sequence. Since development involves complex economic and social factors that are often difficult to predict, careful and rational planning becomes essential. The human factor is identified as a central component of development, serving both as the means and the ultimate goal of the development process. Furthermore, the text highlights the critical role of education and training as prerequisites for sustainable development. Education is increasingly viewed not merely as a cultural or social objective but as a strategic investment that generates significant economic and social returns. Its function extends beyond transmitting societal values to preparing individuals for the profound changes associated with accelerated development. Consequently, educational systems must themselves be planned and managed efficiently to support broader development goals. This perspective has led to the establishment of specialized institutions and programs dedicated to educational planning and its integration with economic and social development strategies. Finally, the passage underscores the fundamental importance of food and agriculture as key sectors in the development process, particularly in developing countries where they remain central to economic growth and social welfare. يؤكد النص أن المجتمعات النامية المعاصرة تسعى إلى تحقيق تقدم اقتصادي واجتماعي سريع من خلال استغلال الموارد المتاحة بأقصى درجات الكفاءة والتنظيم. ويتطلب تحقيق هذا الهدف تخطيطًا منهجيًا يضمن تخصيص الموارد بصورة فعّالة واستخدامها في الوقت المناسب وبالتسلسل الملائم. ونظرًا لأن التنمية تنطوي على عوامل اقتصادية واجتماعية معقدة يصعب التنبؤ بها في كثير من الأحيان، فإن التخطيط الدقيق والعقلاني يصبح أمرًا ضروريًا. كما يحدد النص العنصر البشري بوصفه مكوّنًا أساسيًا في عملية التنمية، إذ يُعدّ في الوقت ذاته وسيلة لتحقيق التنمية والغاية النهائية التي تستهدفها هذه العملية. علاوة على ذلك، يبرز النص الدور الحاسم للتعليم والتدريب بوصفهما من المتطلبات الأساسية للتنمية المستدامة. ويُنظر إلى التعليم بشكل متزايد ليس فقط كهدف ثقافي أو اجتماعي، بل كاستثمار استراتيجي يحقق عوائد اقتصادية واجتماعية كبيرة. وتتجاوز وظيفته مجرد نقل القيم المجتمعية إلى إعداد الأفراد للتغيرات العميقة المرتبطة بالتنمية المتسارعة.وبناءً عليه، ينبغي أن تُخطط النظم التعليمية وتُدار بكفاءة لدعم الأهداف التنموية الأوسع. وقد أدى هذا المنظور إلى إنشاء مؤسسات وبرامج متخصصة تُعنى بالتخطيط التربوي ودمجه مع استراتيجيات التنمية الاقتصادية والاجتماعية. وأخيرًا، يؤكد النص الأهمية الأساسية للغذاء والزراعة بوصفهما قطاعين رئيسيين في عملية التنمية، لا سيما في البلدان النامية حيث يظلان عنصرين محوريين في تحقيق النمو الاقتصادي والرفاه الاجتماعي.